Galerkin Method For Fractional Diffusion Equation - Uçar, Mehmet Fatih; Çağlar, Hikmet (My University, 2016)
The one-dimensional fractional diffusion equation is studied systematically using the Galerkin method. The Caputo fractional derivative is used for formulation. An example is solved to assess the accuracy of the method. The numerical results are obtained for different values (n) of equation. An effective and easy-to-use method for solving such equations is needed.